A new low-temperature hermetic composite edge seal for the fabrication of triple vacuum glazing. (October 2015) - Memon, Saim; Farukh, Farukh; Eames, Philip C.; Silberschmidt, Vadim V.
Abstract: High performance low-cost vacuum glazing is a key development in the move to more energy-efficient buildings. This study reports the results of experimental and theoretical investigations into the development of a new low-temperature (less than 200 °C) composite edge seal. A prototype triple vacuum glazing of dimensions 300mmx300 mm was fabricated with a measured vacuum pressure of 4.8 × 10 −2  Pa achieved. A three-dimensional finite-element model for this prototype triple vacuum glazing with the composite edge seal was also developed. Centre-of-pane and total thermal transmittance values for this small prototype of the triple vacuum glazing were predicted to be 0.33 Wm −2 K −1 and 1.05 Wm −2 K −1, respectively. It was predicted using the developed model that the thermal performance could be improved by reducing the width of the composite edge seal and by the use of soft low-emissivity coatings on the glass surfaces. Detailed three-dimensional isothermal contour plots of the modelled triple vacuum glazing are presented. Highlights: A new hermetic glass-sealing method for vacuum glazing was developed. The low-temperature edge sealing materials were analysed. A novel design and fabrication process was discussed. A vacuum pressure of 4.8 × 10 −2  Pa was achieved with triple-vacuum glazing. A centre-of-pane thermal performance was predicted to be 0.33 Wm −2 K −1 .